(untitled) (Revista Brasileira Multidisciplinar, 2025)
Summary: The development of actions and policies to combat sexual violence occurs through a careful analysis of the numbers of the cases reported by the health services responsible for caring for people in situations of violence. The study aimed to characterize the epidemiological profile of rape cases in the state of Maranhão (2019-2022). Using an ecological approach and data from DATASUS, it identified a predominance of female victims (95.04%), mixed race (72.83%), and an age group of 10 to 14 years (44.43%). "Friends/acquaintances" were the main authors (27.25%), with 79.69% of the author’s life cycle recorded as "ignored". The "residence" was the main location of incidents (69.23%). The results offer a comprehensive view of the sociodemographic panorama of rapes in the state, highlighting the epidemiological importance and contributing to prevention and intervention strategies.